We are what we eat? Eating `against the grain` may not be as beneficial to performance and `economy` in endurance athletes - Bock, J. M.; Kruse, N. T. (The Journal of Physiology, 2017)
During prolonged, submaximal exercise skeletal muscle uses both carbohydrates (CHO) and lipids as substrates to synthesize adenosine triphosphate (ATP), the fundamental unit of energy. The relative contribution of these substrates to fuel pathways depends upon several factors including mode, intensity and duration of exercise, the athlete's training status, and both acute and prolonged dietary intake. With regard to the latter, optimal performance by the athlete is greatly influenced by the combination of adequate fuel stores in relation to the demands of his/her event as well as `metabolic flexibility`, defined in the context of sports performance as the ability to rapidly and efficiently utilize these pathways to maximize ATP synthesis.